PENGEMBANGAN BAHAN AJAR MAHĀRAH AL-KALĀM BERBASIS USLŪB AL-QUR’ĀN - Syaifudin Syaifudin (Tarbiya Islamica, 2020)
Teaching materials are one of the most urgent tools to support the teaching and learning process, without teaching materials the teaching and learning process will not be effective. Currently in schools, teaching materials are available that can be purchased directly from sellers or publishers, but after a close look at many teaching materials that are not yet in accordance with the ideal preparation criteria, it has been proven that teaching materials in Indonesian subjects contain pornographic content. It was also found that Arabic teaching materials contained vocabulary that were not suitable to be taught to students, such as the word "daraba" which means "to hit". Of course this is a big problem in the world of education, and requires preventive steps from teaching staff to deal with these problems thoroughly, one of which is by making independent teaching materials according to the criteria for preparing good teaching materials, and according to the needs of students. The ideal teaching material must pay attention to several principles including the socio-cultural principles, the psychological principles, and the linguistic and educational principles. Mahārah al-kalām is one of the most important Arabic language skills, because basically Arabic is utterance or speech, and not for thought. Therefore, the teaching materials for mahārah al-kalām are arranged according to these principles, one of which is to contain uslub- uslub al-qur'an. Uslūb is etymologically translated as a way, method, method or system. As for the terminology uslub is defined as the meaning contained in the sentence pattern and makes it easier for the reader to read or hear it. Uslub is grouped into three, namely: (1) uslūb 'ilmi (scientific method); (2) uslūb adabi (literary method) and (3) uslūb khitābi (conversational method). The purpose of the three types of uslub above is to make it easier for readers or listeners to the meaning contained in the sentences of the al-quran as well as in the language style. In this article, the author wants to describe teaching materials that contain uslūb al-Qur'ān content.